Implementation of the Duties and Functions of the Intelligence and Security Directorate (Intelkam) of the Central Kalimantan Regional Police in Handling Narcotics Crimes as Transnational Crimes and Their Prevention Efforts - Jehoshapat, Hansel Gavra (Journal of Law, Politic and Humanities, 2026)
Narcotics crime is a global problem that requires a multidimensional approach, considering its characteristics as transnational crimes that cross national borders. The modernization of technology and the development of information flows further complicate the handling of these crimes, with the emergence of increasingly sophisticated modus operandi and a wide network of organizations. Indonesia, especially Central Kalimantan, faces major challenges in addressing illicit narcotics trafficking that threatens public health and social stability. The role of the Directorate of Security Intelligence of the Central Kalimantan Regional Police is very crucial in efforts to prevent and handle cross-border narcotics crimes, considering that this area is a transit route that is prone to narcotics syndicate activities. This study aims to analyze the implementation of the duties and functions of the Central Kalimantan Police Intelligence Directorate in tackling narcotics crimes as transnational crimes, focusing on the effectiveness of inter-agency coordination, the use of intelligence technology, as well as challenges and opportunities in optimizing the role of Intelkam. This study uses a normative approach to understand the dynamics of cross-border narcotics crimes, as well as state efforts to overcome them. The results of the study are expected to provide insight into strategies in overcoming the threat of narcotics trafficking, as well as the importance of inter-agency collaboration in handling cross-border crime in Indonesia.